Ophiocordyceps ovatospora sp. nov. (Ophiocordycipitaceae, Hypocreales), pathogenic on termites from China - Tang, Dexiang; Zhu, Juye; Luo, Lijun; Hou, Donghai; Wang, Zhiqin; Yang, Shidao; Yu, Hong (Phytotaxa, 2022)
A new species, Ophiocordyceps ovatospora, occurring on termites was collected from Yunnan Province, China, and is described based on morphological and molecular phylogenetic data. In a phylogenetic analysis of a combined dataset of multigene loci comprising the internal transcribed spacer regions (ITS), the small and large subunit of the ribosomal DNA (nrSSU and nrLSU), partial sequences of elongation factor 1-alpha (tef-1a) and the largest and second largest subunit of the RNA polymerase (rpb1, rpb2), O. ovatospora was clustered together with O. khokpasiensis to form a clade separate from other species of Ophiocordyceps. Morphologically, O. ovatospora is characterized by producing pseudo-immersed perithecia, filiform asci and ascospores, monophialidic phialides, and oval conidia. Ophiocordyceps ovatospora has smaller perithecia than those of O. khokpasiensis but its asci are larger.